2023
DOI: 10.3390/ph16050660
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Effects of Ulvan Polysaccharides from Ulva rigida

Abstract: One of the main bioactive compounds of interest from the Ulva species is the sulfated polysaccharide ulvan, which has recently attracted attention for its anticancer properties. This study investigated the cytotoxic activity of ulvan polysaccharides obtained from Ulva rigida in the following scenarios: (i) in vitro against healthy and carcinogenic cell lines (1064sk (human fibroblasts), HACAT (immortalized human keratinocytes), U-937 (a human leukemia cell line), G-361 (a human malignant melanoma), and HCT-116… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Tuyun and collaborators reported that plastoquinone derivatives exerted notable cytotoxicity toward colon cancer HCT-116 and breast MCF-7 cells compared to cisplatin [39]. Abdala-Díaz and collaborators reported that ulvan polysaccharides obtained from Ulva rigida demonstrated antiproliferative activity on the HCT-116 tumor cell line [40]. Lokeshwar and collaborators demonstrated that the conjugation of the poor bioavailable antiproliferative compounds Curcumin and dichloroacetate by aminoacidic linkers improves bioavailability and reduced the growth of several breast cancer cell lines and tumor growth and metastasis on transgenic mouse breast cancer (BC) and metastatic BC tumor-bearing mice without showing signs of toxicity [41].…”
mentioning
confidence: 99%
“…Tuyun and collaborators reported that plastoquinone derivatives exerted notable cytotoxicity toward colon cancer HCT-116 and breast MCF-7 cells compared to cisplatin [39]. Abdala-Díaz and collaborators reported that ulvan polysaccharides obtained from Ulva rigida demonstrated antiproliferative activity on the HCT-116 tumor cell line [40]. Lokeshwar and collaborators demonstrated that the conjugation of the poor bioavailable antiproliferative compounds Curcumin and dichloroacetate by aminoacidic linkers improves bioavailability and reduced the growth of several breast cancer cell lines and tumor growth and metastasis on transgenic mouse breast cancer (BC) and metastatic BC tumor-bearing mice without showing signs of toxicity [41].…”
mentioning
confidence: 99%